Systematic analysis of Fc mutations designed to reduce binding to Fc-gamma receptors - Geoff Hale; Jelle De Vos; Alastair Douglas Davy; Koen Sandra; Ian Wilkinson (Taylor & Francis Group, 2024)
Elimination of the binding of immunoglobulin Fc to Fc gamma receptors is highly desirable for the avoidance of unwanted inflammatory responses to therapeutic antibodies and fusion proteins. Many different approaches have been used in the clinic, but they have not been systematically compared. We have now produced a matched set of anti-CD20 antibodies with different Fc subclasses and variants and compared their activity for binding to C1q, Fc-gamma receptors and in cell-based assays. Most of the variants still have significant levels of activity in one or more of these assays and many of them have impaired temperature stability compared with the corresponding wild-type antibody.